Eradicating educational disparities: Challenging deficit based thinking in educators - Barr, Ashley (2025)
The persistent disparity between economically marginalized students and their more affluent peers remains a critical issue in the U.S. education system. This disquisition explores the systemic factors contributing to this disparity, emphasizing the detrimental impact of deficit ideologies perpetuated by influential figures such as Ruby Payne. Through a feminist post-structural lens, the study critiques prevailing educational practices and policies that reinforce classist assumptions and lower expectations for economically marginalized students. The research focuses on Sun Valley Elementary School located in the Piedmont-Triad region of North Carolina, where a significant performance gap exists between economically marginalized students and their peers. The disquisition proposes an improvement initiative grounded in Gorski's equity literacy framework, aiming to transform teacher beliefs and instructional practices. By fostering high expectations and rigorous instructional practices, the initiative seeks to counteract deficit thinking and improve academic outcomes for economically marginalized students. The proposed professional development cycle integrates high cognitive demand tasks to enhance teacher efficacy and student engagement. The study employs a mixed-methods approach, utilizing quantitative and qualitative data to evaluate the effectiveness of the intervention. The anticipated outcomes include a shift in teacher beliefs away from deficit based, classist ideas to an assets-based ideology and improved instructional practices. This research contributes to the broader discourse on educational equity, advocating for systemic changes that promote high expectations and equitable opportunities for all students.